The impact of Brexit on migration from the V4 countries to the UK: migrant strategies: Report from qualitative research 2019-2023 - Wojciech Bedyński; Jana Pecníková; Petra Strnádová; Karel Čada; Ágnes Erőss; Katalin Kovály (University of Warsaw, Centre of Migration Research (CMR), 2023)
The result of the 2016 Brexit referendum came as a shock to European public opinion. It was the first time a country was leaving the structures of the EU. It raised a number of questions and concerns especially in the countries of Central and Eastern Europe, from which thousands of citizens emigrated to the UK after their accession to the EU in 2004 and the opening of the British labor market to them. Brexit changed the status quo and introduced uncertainty. In many cases, it forced decisions that had been postponed for years and was a motivation to regularize residency status, which, thanks to the functioning of migrants within the common European market, had not required any regulation until now. For some migrants, it was a moment to rethink their chosen life strategy, including considering the option of returning to their homeland or moving elsewhere. For others, it was a motivating factor to start obtaining British citizenship. Brexit later proved to be just one of many crisis events, such as the COVID-19 pandemic, the war in Ukraine and rising inflation across Europe, that affected migrants' life strategies. The four Visegrad countries had much in common in history, and together they experienced the problems of the post-1989 period of political and economic transformation, and later went through the process of integration into the European Union. Among the consequences of these processes was a wave of emigration to the United Kingdom, which all V4 countries experienced, albeit to varying degrees. This report on qualitative research conducted between 2019 and 2023 by four research institutions from each of the V4 countries was produced with funding from the International Visegrad Fund. It contributes to a comparative analysis.
Keywords: 330; Brexit; Visegrad Group; migration; life strategy; uncertainty